Development and Validation of Dimensions For Measuring The Relationship Between E-Service Quality and User Satisfaction - ISMAIL AL-NUAIMI, IHAM TARIQ (2017)
Quality of e-service is one of the significant factors that determine the success or failure of organizations. It may contribute to the competitive advantages as well as improve the relationships with the clients. Attaining high e-service quality (e-SQ) and user satisfaction are challenging since they depend significantly on the user perception and expectation, which can be tricky at times. This research deep-dived the quality of e-services offered by five Malaysian Institute of High Learning (IHL) including three public and two private IHL by adopting expectancy disconfirmation theory (EDT) leading to a development of a conceptual model for the relationship between e-SQ and users‘ satisfaction. This theory can measure the customer satisfaction from the differences between customer‘s expectations and experienced of perceived products or services. It was selected because it has a dominated research on consumer satisfaction / dissatisfaction and it has a strong empirical support. This research utilized a quantitative approach to collect and to analyze the gathered data and then to develop the final conceptual model. The software packages used in this study are SPSS 20 and AMOS 21. The research has achieved its objectives in two folds. The first one is to identify significant dimensions of e-SQ in Malaysian IHL by conducting Exploratory Factor Analysis with 110 students in the selected universities. The second fold is to find the relationship between e-SQ dimensions and the user satisfaction by using Structural Equation Modeling (SEM) and conducting Confirmatory Factor Analysis with 320 students in the same IHL. The research results indicated that most of the final dimensions of e-SQ affect users‘ satisfaction positively. These dimensions are information, privacy/security, system availability, reliability and expectancy disconfirmation theory dimensions. Furthermore, the research has led to building a first measurement scale to measure the quality of e-services in higher education, which can assist to improve the performance and effectiveness of e-services hence achieving user satisfaction.